Attenuation of quorum sensing system and virulence in Vibrio cholerae by phytomolecules - Saha, Subhasree; Aggarwal, Shifu; Singh, Durg Vijai (Frontiers in Microbiology, 2023)
Quorum sensing is a cell-to-cell communication pathway that leads to gene expression, signaling molecule accumulation, biofilm formation, and production of virulence factors. Vibrio cholerae, a gram-negative bacterium, is the causative agent of cholera that spread through consumption of contaminated drinking water. The quorum sensing pathway in V. cholerae is regulated by luxO which at low cell density produces major virulence factors that mediates infection. However, biofilm formation and virulence factors is positively regulated by aphA and negatively regulated by hapR. Hence, the global regulator luxO can be viewed as a target to modulate the quorum sensing pathway to diminish V. cholerae pathogenesis. The present study investigated the modulating activity of phytochemicals quercetin and naringenin on biofilm formation in V. cholerae. The anti-quorum sensing capability of the phytomolecules against the model organism Chromobacterium violaceum was determined. These phytomolecules were then used to determine their inhibitory effect on quorum sensing of V. cholerae using flow cytometry, MTT assay, CLSM, and growth curve analysis. The results showed that phytomolecules can modulate QS but do not exhibit anti-bacterial activity. The crystal violet staining assay showed that V. cholerae strains VC287 and N16961 formed thick biofilm. The phytomoleculs showed two-fold reduction in the expression of biofilm-associated genes gbpA, vpsA, rbmA, and mbaA indicating that phytomolecules had QS modulating activity but exhibit non-toxic, non-hemolytic, anti-adhesion and anti-invasion properties. In addition, quercetin and naringenin were more effective compared to the commercially available quorum-sensing inhibitors terrein and furanone C-30. This study thus provides evidence that the phytomolecules quercetin and naringenin modulates the quorum-sensing pathway in V. cholerae that can be used as a therapeutic agent